Design of the Gui based remote on/off control and monitoring single phase automation device / Mohd Suhaimi Sulaiman … [et al.] - Sulaiman, Mohd Suhaimi; Annuar, Ishak; Muhammad, Ahmad Nurrizal
The Microcontrollers are very popular in electronics and computer controlled systems overall in the world. Remote control of a system by using computers is applied to lots of processes. It is very important about reducing the time loss and also cost of employees. This thesis presents the controlling of a microcontroller based system using computer. First of all microcontrollers are introduced. The main differences between microcontrollers and microprocessors are discussed with reasons. Also, the reasons of why PICs (Peripheral Interface Controller) are the most popular type of the microcontrollers are explained. The hardware and software parts of microcontroller are clarified comprehensively. One of the most important parts of this thesis is the communication between PIC microcontroller and computer, so communication protocol is described in depth. PIC MPASM is used for programming PIC microcontroller and Visual Basic is used for programming the computer. The thesis concludes with explanations ofthese programs.